FUNGSI DIGITAL FORENSIK BAGI SATRESKRIM POLRES AGAM DALAM PENYIDIKAN TINDAK PIDANA JUDI ONLINE - Algino Ganaro (LPPM Universitas Ekasakti Padang, 2020)
The function of Digital Forensics in Online Gambling Crime Investigation by the Agam Police Criminal Investigation Unit is to obtain evidence of an online gambling crime by knowing who did it, what was done, what software was used, what process results were used and when to do it . In online gambling crimes that occur in the jurisdiction of the Agam Police, evidence collected through digital forensics is in the form of information on gambling crimes carried out by examining sites that are used as a means or place for gambling. Constraints in Using Digital Forensics in Online Gambling Crime Investigation By Satreskrim Agam Police is the address of most online gambling websites located abroad and made by foreign countries, bank accounts are always changing. The application data for opening a bank account that is used to accept online gambling transactions is fictitious, evidence is easy to change and is lost, the high level of knowledge of the actors about information technology and the lack of public awareness and concern for online gambling.